PTH-106 Bile Acid Diarrhoea Masquerades As Diarrhoea-predominant Irritable Bowel Syndrome: Results From A Dual Centre Prospective Study. (9th June 2014) - Aziz, I; Mumtaz, S; Bholah, H; Chowdhury, FU; Sanders, DS; Ford, AC
Abstract : Introduction: Several studies have suggested that bile acid diarrhoea (BAD) can present with symptoms that are compatible with diarrhoea-predominant irritable bowel syndrome (IBS-D). However, uncertainty exists as these have often been retrospective, have not defined IBS-D according to accepted diagnostic criteria, or have included patients with chronic diarrhoea in the analysis. We have examined this issue in a well-characterised cohort of patients with rigorously defined IBS-D. Methods: This was a prospective cross-sectional survey conducted among consecutive patients with IBS-D attending Gastroenterology clinics in two hospitals in Sheffield and Leeds, UK. All patients underwent 23-seleno-25-homo-tauro-cholic acid (SeHCAT) scanning according to local protocol, with a retention of <15% at day 7 used to confirm BAD. The degree of BAD was classed as severe if retention < 5%, moderate if 5.0 >9.9%, and mild if 10.0 >14.9%. Presence of IBS-D was defined according to the Rome III criteria. Patients with other known risk factors for BAD, including previous cholecystectomy, terminal ileal Crohn's disease, terminal ileal resection, pelvic or abdominal radiotherapy, coeliac disease, or microscopic colitis, were excluded. Participants completed the patient health questionnaire-15, a validated somatisation score, and the hospital anxiety and depression score. Demographic data, including age, gender, lifestyle, and body mass index (BMI) were collected. The effect of all these factors on presence or absence of BAD was examined by multivariate logistic regression analysis, with results expressed as odds ratios (ORs) with 99% confidence intervals. Results: This is an interim analysis of an ongoing study. In total, 51 patients with IBS-D according to the Rome III criteria have been recruited to date (37 (72.5%) female, mean age 47.0 years). In total, 14 (27.5%) were found to have BAD following SeHCAT scanning. Of these, nine (17.6%) had severe BAD, four moderate, and one mild. Mean age, BMI, anxiety, depression, and somatisation scores were not significantly different among those with, compared with those without, BAD. No predictors of presence of BAD were identified following multivariate logistic regression. Conclusion: Our data suggest that more than one-in-four IBS-D patients, if investigated, have definite evidence of BAD. In the majority, this is severe. Failure to investigate patients to exclude BAD as an underlying cause of symptoms compatible with IBS-D results in misdiagnosis and a failure to institute effective therapy, in the form of bile acid sequestrants. This suggests that future IBS management guidelines should advocate diagnostic testing to exclude BAD before a diagnosis of IBS-D is made. Disclosure of Interest: None Declared.